Therapeutic Endoscopic Retrograde Cholangiopancreatography for Pediatric Hepato-Pancreato-Biliary Diseases: A Systematic Review and Meta-Analysis - Sun, Rongjuan; Xu, Xiaodan; Zheng, Qipeng; Zhan, Jianghua (Frontiers in Pediatrics, 2022)
Background: Hepato-pancreato-biliary (HPB) disease has different causes and types between children and adults, which have been diagnosed increasingly in the pediatric group. Endoscopic retrograde cholangiopancreatography (ERCP) has been gradually considered as a therapeutic method in adults, while in pediatric patients, there are not many reports of its usage. This systematic review and meta-analysis aims to assess the use condition of therapeutic ERCP in the management of pediatric HPB diseases. Methods: This systematic literature search was conducted in the PubMed、Embase、Web of Science and the Cochrane library databases to identify all relevant articles published from inception to February 2022 that evaluated therapeutic ERCP in pediatric patients with Hepato-Pancreato-Biliary diseases. The researchers included studies that patients were less than 18 years old and underwent therapeutic ERCP procedures. A random-effects model was used to analyze the usage rate of therapeutic ERCP-procedures, procedural success rates, adverse events rates, and the rate of different therapeutic procedures. Subgroup analysis, sensitivity analysis, and meta-regression were conducted to analyze the source of heterogeneity. Results: A total of 33 articles were included. After homogenization, the overall usage of therapeutic interventions accounts for 77% (95%CI74%-81%) in all ERCP procedures. After excluding outlier studies, the estimation of therapeutic procedure success rate is 74% (95% CI 69 %-79%), adverse events rate is 8% ( 95% CI 6 %-10%). In our study, stent placement is the most common procedure which makes up 75% (95%CI 65%-86%) of all therapeutic procedures. In addition, the usage proportion of sphincterotomy (ST), stone extraction/removal, bougienage/Balloon dilation is respectively 46% (95% CI 39 %-53%), 34% (95% CI 31%-38%), and 26% (95% CI 22%-29%). Conclusions: ERCP procedure is gradually considered as a therapeutic technique in pediatric patients, the proportion of therapeutic ERCP is 77% of total usage, which is increasing by the year. Meanwhile, its success rate is relatively high. It reflects that this operation modality is promising in the treatment of Hepato-pancreato-biliary disorders and is gradually expanded as more branch technologies are being used. A variety of operations can be achieved through ERCP procedures, and more functions should be developed in the future.